Linking biochar physico-chemical traits to sorghum growth and soil carbon dynamics - Shembo, Alemayehu K.; Geremew, Addisie; Guthrie, De’Zarae M.; Elder, Debra; Woldesenbet, Selamawit; Grady, Tony; Shrestha, Ambar; Amarasekara, Ananda; Ray, Ram L.; Kuloyo, Olukayode; Davies, Christian; Mugundan, Jaison; et al. (Frontiers in Environmental Science, 2025)
Biochar (BC) is an eco-friendly soil conditioner that mitigates climate change and promotes sustainable agriculture. However, selecting the appropriate commercial biochar and its application for specific soil and crop types requires research. The present work explores the effects of two commercial biochars (BC-I and BC-II) on sorghum plants grown in sandy loam soil under greenhouse conditions. The study characterized the morphological and chemical properties of BCs, including structure, surface area, porosity, elemental composition, and functional groups. Sorghum plants were cultivated in soil amended with biochar at varying application rates of 2.5%, 5%, 10%, and 15%, corresponding to 7, 14, 28, and 42 tons per hectare, respectively. Plant performance was evaluated using chlorophyll content (SPAD), relative water content (RWC), Leaf area (LA) and biomass. Soil carbon content was analyzed using elemental and total organic carbon analysis. Macro- and micronutrients content in soils were also determined. Our findings suggest that compared to BC-II, BC-I exhibited a higher abundance of surface functional groups, greater micropore volume, and a significantly larger pore surface area, indicating its superior physicochemical properties. Except for the 2.5% application rate, all other biochar (BC) rates (namely, 5%, 10%, and 15%) significantly enhanced soil carbon content. Notably, the 5% application rate resulted in the most substantial improvement in soil nutrient levels, including calcium (Ca), potassium (K), magnesium (Mg), and phosphorus (P), compared to the other rates. Sorghum plants treated with lower application rates (2.5% and 5%) of both BC-I and BC-II exhibited significantly enhanced RWC, chlorophyll content, and shoot biomass compared to those treated with higher rates (10% and 15%). Among these, the 5% composite BC-I application demonstrated the most consistent improvement in plant physiological traits (RWC and SPAD) and growth parameters (LA and biomass). However, neither BC variants significantly improved soil nitrogen levels. Our findings indicate that a 5% application rate of composite BC-I provides the most effective balance between enhancing plant performance and improving soil quality in sandy loam soil. Future research on biochar production efforts should prioritize blending this biochar with nitrogen-rich organic fertilizers to address nitrogen limitations and further enhance soil fertility.